Case Report: Pericardial Tamponade and Hemothorax After Superior Vena Cava Filter Removal - Zeng, Xueping; Zhou, Jin; Zhou, Qidi; Huang, Zhigang (Frontiers in Cardiovascular Medicine, 2022)
A 67-year-old male patient was admitted to receive surgical treatment because of lumbar spinal stenosis. Ultrasonography showed a thrombus in the middle and lower segment of the left internal jugular vein. Superior vena cava filter implantation was performed and removed on day 7 after its implantation. The patient suddenly had dyspnea, and his blood pressure decreased 9 hours after filter removal. Examinations showed pericardial tamponade and hemothorax. In addition, aortic dissection occurred approximately 20 days after superior vena cava filter removal. This case aimed to provide information to clinicians about the complications of the implantation and removal of superior vena cava filter implantation. The safety and possible complications of superior vena cava filter implantation and removal should be evaluated to identify their actual clinical benefit and cost-effectiveness ratio.